Comparative analysis of female athlete biathletes' sports results in World Cup competitions before the World Chamionship and during the World Championship in the season of 2010-2011 - Koèergina, N.; Èepulenas, A.; Zuoza, A. (Education. Physical training. Sport, 2012)
Research background and hypothesis. Modern training trend for biathletes is the increasing intensity of the training process in competition activities. Competition activities of elite biathletes while preparing for the main competition of the season have received little attention by researchers. Research hypotheses: The number of starts and sports results in the competitions before the main competition of the season for elite biathletes are related to sports results in the main competition of the season. Research aim was to analyse the interaction of biathletes` sports results and the number of starts, and to establish the relation of this interaction between the results achieved in World Cup competitions and World Biathlon Championship. Research methods. The data have been retrieved from the documents of the International Biathlon Union (IBU): protocols of the World Biathlon Championship of 2011 and World Biathlon Cup competition. We analysed the sports results of female biathletes who took the 1st-10th places in the World Biathlon Championship in individual events. Research results. World elite biathletes participated in E.ON and IBU category competitions 16.2 ± 3.74 times before the World Biathlon Championship. The number of starts correlates with the places taken by biathletes in the general account of the World Biathlon Cup before the world championship (r = -0.83). In the individual races in the World Championship, all medals were won by eight skiers, and five of them were among the first ten skiers in the general standing of World Cup competitions before the world championship. Discussion and conclusion. The preparation of elite biathletes for the most important competition of the season - World Biathlon Championship is grounded on the repeated participation in the World Biathlon Cup competitions. Biathletes, taking the 1st-10th places in the general account of the World Biathlon Cup, are real applicants for medals in the World Biathlon Championship.